Integrating the Communication and Medicine in the Teaching of Community Communication: an Innovative Brazilian Experience - Mesquita, Giovana (2020)
Is it possible to have an interdisciplinarity between Communication and Health courses in the teaching of Community Communication? Theoretically, some authors, especially in the field of health, already discuss this integration (Araújo & Cardoso, 2007). But beyond a bibliographical production, this integration is almost non-existent in Brazilian classrooms. Thus, the objective of the article is to share an interdisciplinary experience in the teaching of Community Communication, with emphasis on citizenship practices, involving the Communication and Medicine courses of a public university located in Northeast Brazil. We are aligned with Peruzzo (2013, p. 176) in the understanding that the Community Communication “contributes to the formation of citizens capable of understanding the world and organizing itself to transform it”.